Identification and validation of miRNAs as endogenous controls for RQ-PCR in blood specimens for breast cancer studies. - Ailbhe M McDermott (PLoS ONE, 2013)
INTRODUCTION: A prerequisite to accurate interpretation of RQ-PCR data is robust data normalization. A commonly used method is to compare the cycle threshold (CT) of target miRNAs with those of a stably expressed endogenous (EC) miRNA(s) from the same sample. Despite the large number of studies reporting miRNA expression patterns, comparatively few appropriate ECs have been reported thus far. The purpose of this study was to identify stably expressed miRNAs with which to normalize RQ-PCR data derived from human blood specimens. METHODS: MiRNA profiling of approximately 380 miRNAs was performed on RNA derived from blood specimens from 10 women with breast cancer and 10 matched controls. Analysis of mean expression values across the dataset (GME) identified stably expressed candidates. Additional candidates were selected from the literature and analyzed by the geNorm algorithm. Further validation of three candidate ECs by RQ-PCR was performed in a larger cohort (n = 40 cancer, n = 20 control) was performed, including analysis by geNorm and NormFinder algorithms. RESULTS: Microarray screening identified 10 candidate ECs with expression patterns closest to the global mean. Geometric averaging of candidate ECs from the literature using geNorm identified miR-425 as the most stably expressed miRNA. MiR-425 and miR-16 were the best combination, achieving the lowest V-value of 0.185. Further validation by RQ-PCR confirmed that miR-16 and miR-425 were the most stably expressed ECs overall. Their combined use to normalize expression data enabled the detection of altered target miRNA expression that reliably differentiated between cancers and controls in human blood specimens. CONCLUSION: This study identified that the combined use of 2 miRNAs, (miR-16 and miR-425) to normalize RQ-PCR data generated more reliable results than using either miRNA alone, or use of U6. Further investigation into suitable ECs for use in miRNA RQ-PCR studies is warranted.